PENGARUH KEAKTIFAN SISWA DALAM PEMBELAJARAN DAN PRAKTEK KERJA LAPANGAN TERHADAP KEMAMPUAN KOMUNIKASI INTERPERSONAL SISWA KELAS XII JURUSAN ADMINISTRASI PERKANTORAN SMK NEGERI 1 SURAKARTA - Hikmah, Mamluatul; Santosa, Djoko; Subarno, Anton (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2015)
The objectives of this research are to investigate: (1) the significant effect of learning activeness on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014; (2) the significant effect of field work practice on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014; and (3) the simultaneous effect of learning activeness and field work practice on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014.This research used the descriptive quantitative research method. Its population was all of the students as many as 77 in Grade XII of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2014/2015. The samples of research consisted of 44 students. They were taken by using the proportional random sampling technique. The data of research were collected through questionnaire and documentation. They were analyzed by using the multiple linear regression analysis aided with the computer program of SPSS17.The results of research are as follows: (1) the learning activeness has a significant effect on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014 as indicated by the value of tcount = 2.045 > that ttable = 1.682; (2) the field work practice has a significant effect on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014 as shown by the value of tcount = 3.737 > thatof ttable = 1.682; and (c) the learning activeness and field work practice have s simultaneously significant effect on the personal communication ability of the students in Grade XII of Office Administration Department of State Vocational High School 1 of Surakarta in Academic Year 2014/2014 as specified by the value of Fcount = 11.537 > that of Ftable = 3.230. The regression equation is ? = 6.064 + 0.216 X1 + 0.257 X2. The relative contribution of the learning activeness (X1) is 72.5%, and its effective contribution is 9.9%. Meanwhile, the relative contribution of the field work practice (X2) is 27.5%, and its effective contribution is 26.1%.